An international phase 3 trial in head and neck cancer: Quality of life and symptom results. Issue 3 (25th October 2013) - Bottomley, Andrew; Tridello, Gloria; Coens, Corneel; Rolland, Frederic; Tesselaar, Margot E.T.; Leemans, C. Rene; Hupperets, Pierre; Licitra, Lisa; Vermorken, Jan B.; Van Den, Danielle; Truc, Gilles; Barillot, Isabelle; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND The European Organization for Research and Treatment of Cancer (EORTC) 24954 phase 3 randomized clinical trial compared 2 schemes of combined chemotherapy for patients with resectable cancers of the hypopharynx and larynx: sequential induction chemotherapy and radiotherapy versus alternating chemoradiotherapy. The current study reports detailed effects of both treatment arms on health‐related quality of life (HRQOL) and symptoms. METHODS A total of 450 patients aged 35 years to 76 years (World Health Organization performance status (WHO PS) ≤ 2) with untreated, resectable advanced squamous cell carcinoma of the larynx (tumor classification of T3‐T4) or hypopharynx (tumor classification of T2‐T3‐T4) with regional lymph nodes in the neck classified as N0 to N2 with no metastases were randomized in this prospective phase 3 trial into either the sequential arm (control) or the alternating arm (experimental). QOL assessment was performed at randomization; at baseline; at 42 days; and at 6, 12, 24, 36, and 48 months. RESULTS There were no observed differences with regard to the primary endpoint of Fatigue and secondary endpoint of Dyspnea. Significant differences were found in the secondary endpoints of Swallowing and Speech problems at 42 days after randomization in favor of patients in the sequential arm. Explanatory and sensitivity analysis revealed that the primary analysis favored the sequential arm, but the majority of differences in HRQOL did not exist at the end of treatment, and returned to baseline levels. CONCLUSIONS In the current study, a trend toward worse scores was noted in the patients treated on the alternating chemoradiotherapy arm but very few differences reached the level of statistical significance. The HRQOL scores of the majority of patients returned to baseline after therapy. Cancer 2014;120:390–398. © 2013 American Cancer Society.